Oil Factor in US Foreign Relations (1980-1970) - Noman, Nijyar N. (Humanities Journal of University of Zakho, 2017)
The US has made many kinds of relations worldwide, these relations developed greatly since the World War II in particular. On the ground of these crucial relations, some scholars have taken these relations into account. Hence, this study is narrated according to this crucially as well. Thus, having chosen the oil for this research is considered to be a main factor of the US foreign relations. From my perspective, this study will be taking higher consideration in the upcoming academic studies. In the light of this preponderant factors of US foreign relations. The significant of oil topic is known as a main actor in the US foreign relations. In this period many developments had taken place at the diplomatic levels between the exporting and importing petroleum states. As a result, this in some aspects had affected the Arab world even internationally.